Arterial cardiovascular diseases and risk of venous thromboembolism - Rinde, Ludvig Balteskard (Journal of Thrombosis and Haemostasis, 2018)
Despite differences in epidemiology, pathology, and treatment, growing evidence suggests a bidirectional relationship between venous thromboembolism (VTE), a collective term for pulmonary embolism (PE) and deep vein thrombosis (DVT), and arterial cardiovascular diseases (CVD, i.e., myocardial infarction [MI] and ischemic stroke). The aim of this thesis was to investigate the impact of atherosclerosis, MI and ischemic stroke on the risk of incident VTE. Additionally, we aimed to investigate the effect of prothrombotic genotypes and ischemic stroke on the risk of VTE. We recruited study participants from the Tromsø Study, a population-based, prospective cohort study. In all four papers, we used participants from the fourth, fifth and six survey of the Tromsø Study. In paper I, the participants consisted of a subgroup from the Tromsø Study with a more extensive examination, including ultrasonography of the carotid artery. In paper IV, a subgroup of participants with extended genetic analysis was included. We found no association between the formation or progression of asymptomatic atherosclerosis and risk of VTE in time-varying analyses. However, MI and ischemic stroke were associated with a transient risk of VTE after adjusting for potential confounding factors. The study participants with MI had a particularly high risk of developing PE. After both MI and stroke, the risk was particularly high for provoked VTE events. The proportion of patients immobilized before the VTE event was substantially higher in those with compared in those without stroke. We also found a synergistic effect of ischemic stroke and prothrombotic genotypes on the risk of VTE. The risk increased gradually with the number of risk alleles. Our findings imply that incident MI and ischemic stroke are associated with an increased transient risk of VTE, and that genetic risk factors are important in the development of VTE after stroke. The transient nature of the VTE risk suggests that indirect (e.g., hospitalization, immobilization) or direct ...